Mémento de l'assainissement - Gabert, Julien (éditions Quae, 2018)
This Handbook is a methodological and practical guide for putting liquid sanitation services into operation in the Southern countries. It covers the entire wastewater and sludge collection and treatment chain in rural, semi-urban and urban contexts. Discover the website dedicated to this handbook: http://memento-assainissement.gret.org